NOD1, NOD2, PYDC1, and PYDC2 gene polymorphisms in ovarian endometriosis - Kula, Hakan; Balbal, Beste; Timur, Tunc; Yalcın, Pelin; Yavuz, Onur; Kızıldag, Sefa; Ulukus, Emine Cagnur; Posaci, Cemal (Frontiers in Medicine, 2025)
BackgroundEndometriosis, a prevalent chronic gynecologic disorder, significantly impacts women’s health, with both genetic and environmental factors contributing to its heritability. Within the adaptive immune system, the NOD-like receptors (NLR) pathway plays pivotal roles in various autoinflammatory diseases, regulating interleukins, proinflammatory cytokines, and NF-κB activity. However, the potential association between single nucleotide polymorphisms (SNPs) of the NOD1, NOD2, PYDC1, and PYDC2 genes and the predisposition to endometriosis risk remains unexplored.MethodsIn this cross-sectional study, 54 patients diagnosed with ovarian endometriosis and 54 control subjects were included. The genetic SNPs of NOD1 (rs2075820 and rs2075818) and NOD2 (rs104895461) were assessed using the PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) method. Additionally, the polymorphisms of PYDC1 and PYDC2 were evaluated using Sanger sequencing. After conducting polymorphism analysis, the genetic profiles were assessed with the clinical manifestations and the size of ovarian endometriomas, categorized as either small (<4 cm) or large (≥4 cm).ResultsSignificant differences in the NOD1 rs2075820 (G: A) genotypes were found. The GG genotype was more prevalent in endometriosis patients (p = 0.04), while the GA genotype was less common (p = 0.029). The AA genotype was associated with higher rates of perimenstrual gastrointestinal symptoms (p = 0.005) and infertility (p = 0.037). The PYDC2 rs293833 variant was detected in 22.2% of patients. Carriers of this variant exhibited higher rates of perimenstrual gastrointestinal symptoms (p = 0.004), infertility (p = 0.001) and larger endometriomas (≥4 cm) (p < 0.001). No significant differences were found in NOD1 rs2075818 genotypes (p = 0.89) and no polymorphisms were detected in NOD2 or PYDC1 genes.ConclusionThese findings emphasize the influence of genetic polymorphisms on the clinical manifestations of endometriosis. Specifically, gene polymorphisms in NLRs have been found to significantly impact infertility and increase endometrioma size.